OPTIMALISASI WAKTU PROYEK DENGAN MENGGUNAKAN METODE CPM DAN PROBABILITAS WAKTU 3 DURASI (Studi Kasus Proyek Pembangunan Mall Laves Grand Sungkono Lagoon Surabaya) - Muhammad Chilmi; Diah Ayu Restuti Wulandari (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2020)
There is many aspects of uncertainty on the project has led to accuracy in the preparation of the project schedule, Leading to the need scheduling analysis with probability 3 duration so that the different as a supporter who affect in duration total settlement in a project can be controlled and are not too late .An arrangement of scheduling existing on the project mall laves proven cause place aside of uncertainties aspects, so with using cpm method and probability of 3 duration to find the end of the project total duration of the most effective and efficient, the existing of project duration is 500 days the project start on 7 july 2018 and end on 1 december 2019 change into 694 days total duration and project start on the same existing duration project is on 6 july 2018 and end on 26 september 2020 with the deviation time of the day or about 194 days or around 6,5 month. The activities thats on the critical line is structure installment activities (like concrete foundation, concrete beam, concrete column, slab and concrete emergency ladder), ground activities (like cutting of the head of pile),elevator installment activities.